2020
DOI: 10.1002/lary.28970
|View full text |Cite|
|
Sign up to set email alerts
|

Low‐Normal Platelets and Decreasing Platelets Are Risk Factors for Hearing Impairment Development

Abstract: Identification of undefined risk factors will be crucial for the development of therapeutic strategies in hearing impairment. Platelets are likely to affect the development of sudden sensorineural hearing loss, which is a primary risk factor for permanent hearing impairment. This implies that abnormal platelets might contribute to long-term hearing loss. This study investigated the role of platelets in the development of hearing impairment over a 5-year period. Methods: This study was a retrospective cohort st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…In a study of 1,897 participants, Abe et al [14] investigated the correlation between PLT and the development of hearing impairment over a five-year period. They found that a low to normal PLT correlates with a low-frequency hearing impairment, and a decreasing PLT in low to normal platelet subjects is an independent risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 1,897 participants, Abe et al [14] investigated the correlation between PLT and the development of hearing impairment over a five-year period. They found that a low to normal PLT correlates with a low-frequency hearing impairment, and a decreasing PLT in low to normal platelet subjects is an independent risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiologic studies support significant links between hearing-loss development and vascular risk factors such as dyslipidemia and diabetes [5,6]. Furthermore, recent studies have noted that low or declining platelet levels are also important and novel risk factors for the development of hearing loss [7]. Managing these risk factors is crucial to prevent the development of hearing impairment, since no effective drug therapies are approved that are capable of protecting or restoring hearing, and treatment for hearing loss is limited to clinical devices [4].…”
mentioning
confidence: 96%